The Effect of Nonbinding Agreements on Cooperation among Forest User Groups in Nepal and Ethiopia - Dannenberg, Astrid (World Bank, Washington, DC, 2015)
This paper summarizes the results from public goods experiments investigating the effect of nonbinding agreements on cooperation. Unlike previous studies, this experimental study was conducted among members of forest user groups in Ethiopia and Nepal with long histories of social interdependence. These countries are also characterized by a high degree of collectivism. Overall, the results show a weak effect of nonbinding agreements on cooperation in the two locations. The main reason for this is that the cooperation level is relatively high even without an agreement and only a small proportion of subjects change their behavior when the agreement option is introduced. Nonetheless, the research indicates that the willingness to enter an agreement varies between subjects and strongly correlates with their cooperativeness.